Пусть длина х, тогда ширина х-4.
х(х-4)=(х-3)(х-2)+6
х*х-4х=х*х-5х+6+6
х=12-длина прямоугольника
тогда ширина 12-4=8.
х² + х -30 ≤ 0
х² -х -20 ≥ 0
ищем корни квадратных трёхчленов:
х² + х -30 = 0 корни -6 и 5
х² -х -20 = 0 корни 5 и -4
-∞ [-6] [-4] [5] +∞
+ - - + знаки х² + х -30
+ + - + знаки х² -х -20
решение системы
ответ: х∈[-6; -4]
х² + х -30 ≤ 0
х² -х -20 ≥ 0
ищем корни квадратных трёхчленов:
х² + х -30 = 0 корни -6 и 5
х² -х -20 = 0 корни 5 и -4
-∞ [-6] [-4] [5] +∞
+ - - + знаки х² + х -30
+ + - + знаки х² -х -20
решение системы
ответ: х∈[-6; -4]
шир x -4 длина x S=x*(x-4) (x-2)*(x-3)=x*(x-4)-6 x^2-4x+6=X^2-5x-6
X=12 (дм) длина 12-4=8 ширина